Ranger the Kaimanawa stallion - Wilson, Kelly, 1989-; Cooper, Jenny, 1961- (New Zealand ; Penguin, 2016)
"Ranger is a wild horse living in the rolling Kaimanawa Ranges of New Zealand. The leadstallion of a large herd, he protects his mares and foals from danger and takes them tosafe places to graze among the tussock. One wintery day, Ranger hears the sound of a helicopter approaching. The Kaimanawa horses don't trust humans and Ranger has always kept his herd well away from them. He rounds up the others to flee, but after hours of being mustered by helicopter, he finds himself locked in a pen with over a hundred frightened horses. This will be his very last day in the wild. But it's also the first day of a completely new life, a life that Ranger at first finds frightening and confusing. But, with the gentle and patient care of the three sisters who have rescued him, it's a life that Ranger will eventually grow to love"--Provided by publisher.
Picture story book for children.
Junior, primary
Keywords: Wild horses -- Juvenile fiction; Horses -- Juvenile fiction; Animals -- Juvenile fiction; Wild horses -- New Zealand -- Kaimanawa Mountains -- Juvenile fiction; Children's stories, New Zealand